(untitled) (Research, Society and Development, 2022)
Researches has reported some factors that may be associated with traffic accidents involving cyclists. This study aims to analyze the factors associated to traffic accidents involving cyclists and motor vehicles. A integrative review of the literature was carried out between January 2010 and November 2020, using the search strategy PECOS, based on MEDLINE, LILACS and SciELO, using different combinations of keywords. Studies that analyzed the factors associated to traffic accidents involving cyclists and motor vehicles were included. The articles was assessed with the STROBE Initiative. Twelve articles were selected for analysis, which showed diversity in relation to the types of study, sample size and instruments and sources for data collection. In general, male gender, types of maneuvers, personality and behavior characteristics, speed limit and not wear a helmet stand out as factors associated to accidents involving cyclists and motor vehicles. Several factors were observed that could be controlled or avoided in accidents of this type. The importance of implementing preventive measures is highlighted, in order to ensure greater safety for cyclists.